2013
DOI: 10.3329/bmrcb.v38i3.14331
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative serum parathyroid hormone level is an indicator of hypocalcaemia in total thyroidectomy patients

Abstract: Postoperative hypocalcaemia is the most frequent and common complication after total thyroidectomy. It is necessary to diagnose or to predict hypocalcaemia immediately after total thyroidectomy for minimizing complications. A prospective observational study was carried out in the Department of Clinical Pathology in collaboration with Department of Microbiology & Immunology, Department of Surgery, Department of Otolaryngology, Bangabandhu Sheikh Mujib Medical University (BSMMU) and Department of Otolaryngology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Low post-operative PTH was found to have a statistically significant association with transient biochemical hypocalcaemia in 24 studies, 1033 compared with 3 studies where there was not a statistically significant result 34–36 . Low intra-operative PTH levels and a larger differential PTH from the pre-operative to post-operative stage were also seen to have statistically significant associations in 2 studies 37,38 and 13 studies 10,12,14,15,22,23,27,29,31,36,39–41 , respectively. Pre-operative PTH showed a non-significant association with transient biochemical hypocalcaemia in the majority of studies.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Low post-operative PTH was found to have a statistically significant association with transient biochemical hypocalcaemia in 24 studies, 1033 compared with 3 studies where there was not a statistically significant result 34–36 . Low intra-operative PTH levels and a larger differential PTH from the pre-operative to post-operative stage were also seen to have statistically significant associations in 2 studies 37,38 and 13 studies 10,12,14,15,22,23,27,29,31,36,39–41 , respectively. Pre-operative PTH showed a non-significant association with transient biochemical hypocalcaemia in the majority of studies.…”
Section: Resultsmentioning
confidence: 81%
“…Low post-operative calcium was the only other commonly assessed biochemical factor that showed a statistically significant positive association with transient biochemical hypocalcaemia in the majority of studies. 12,13,22–24,27,28,31,32,36,37,39,44,45 Positive associations were shown with post-operative calcitonin and post-operative albumin but in only one study. 18 Pre-operative vitamin D, magnesium, phosphate, creatinine, calcitonin and thyroid-stimulating hormone levels showed non-significant associations in the majority of studies where investigated.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…17 8 where male was 35 (22%) and female 125 (78%), the mean age was 49.4 ± 14 years, ranged 18 to 86 years. Islam 9 reported mean age was 39 ± 13.18 with ranged 15 to 75 years and in his study also found female predominant; with male 22.5% and female 77.5%. In a review of the literature, there are different definitions of postoperative hypo-parathyroidism after thyroidectomy, mostly based on serum calcium levels.…”
Section: 12mentioning
confidence: 60%
“…Among them 16 hypocalcaemia were developed after 24 hours and 45 were developed after 48 hours of total thyroidectomy. Islam et al 9 in their study, the incidence of hypocalcaemia found 38.5% and post-operative hypocalcaemia found in 25 cases. Simon Grodski 8 found 26% hypocalcaemia in his study.…”
Section: 12mentioning
confidence: 82%